2017
DOI: 10.1111/psyp.12872
|View full text |Cite
|
Sign up to set email alerts
|

Resting sympathetic arousal moderates the association between parasympathetic reactivity and working memory performance in adults reporting high levels of life stress

Abstract: The neurovisceral integration model stipulates that autonomic function plays a critical role in the regulation of higher-order cognitive processes, yet most work to date has examined parasympathetic function in isolation from sympathetic function. Furthermore, the majority of work has been conducted on normative samples, which typically demonstrate parasympathetic withdrawal to increase arousal needed to complete cognitive tasks. Little is known about how autonomic regulation supports cognitive function in pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 69 publications
5
29
0
Order By: Relevance
“…Significant correlations between the HF‐HRV block effect and the N1 block effect were found. This is in line with previous studies in which HF‐HRV has been shown to be related to arousal level (Giuliano et al, ; ). HRV provides valuable information about the capacity of the organism to effectively function in a complex environment (Thayer et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…Significant correlations between the HF‐HRV block effect and the N1 block effect were found. This is in line with previous studies in which HF‐HRV has been shown to be related to arousal level (Giuliano et al, ; ). HRV provides valuable information about the capacity of the organism to effectively function in a complex environment (Thayer et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…What evidence does exist suggests that studies of samples characterized by sociodemographic risk report smaller effect sizes between RSA and cognitive function than studies not reporting sociodemographic risk (Holzman & Bridgett, 2017). Similarly, we have previously demonstrated that RSA reactivity shows stronger associations with cognitive function in adults reporting lower levels of cumulative life stress and whom have lower resting sympathetic nervous system activity, relative to adults reporting higher life stress with higher sympathetic activity at rest (Giuliano, Gatzke-Kopp, Roos, & Skowron, 2017). Therefore, we predict that relationships between RSA and IC observed here will be less pronounced in children with higher cumulative risk exposure.…”
mentioning
confidence: 62%
“…Studies were excluded if participants with psychopathology were screened out (which would leave only healthy controls), had medical conditions that affect RSA (obesity, cardiovascular disease), or were younger than age 18 years. Participants with eating disorders were also excluded, given effects of excessively low and high body mass index (BMI) on RSA (Fraley, Birchem, Senkottaiyan, & Alpert, 2005;Galetta et al, 2003). Although not all eating disorders are defined by altered BMI, all eating-disordered samples were excluded to avoid potential confounds.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…We also focused on bivariate associations between RSA reactivity and psychopathology. Some studies have examined interactions between psychopathology and (a) resting RSA and RSA reactivity (Hinnant & El-Sheikh, 2013;Yaroslavsky et al, 2013), and (b) both RSA and measures of sympathetic nervous system responding (Giuliano, Gatzke-Kopp, Roos, & Skowron, 2017). Given few examples of such studies, we could not include them.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%